3 * ( y + 2) = 3 y + 6
2007-12-12 07:58:11
·
answer #1
·
answered by Rob 3
·
0⤊
0⤋
need the complete problem. There has to be another integer = to something.
3Y+6=12?
3(2)+6=12
2007-12-12 15:51:14
·
answer #2
·
answered by w_woody 3
·
0⤊
0⤋
Expression
or
3y + 6 = 0
3y = -6
y = -6/3
y= -2
2007-12-12 17:27:07
·
answer #3
·
answered by Dhilip B 1
·
0⤊
0⤋
3(y+2)
2007-12-12 15:54:48
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
3(y+2)
2007-12-12 15:54:46
·
answer #5
·
answered by Wing commander 3
·
0⤊
0⤋
that's been factorised as far as it can go
without any + expression, you cannot get a definite answer, there are millions of possibilities, so it just stay's as 3y+6
2007-12-12 15:54:23
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
if u have 3y u add the 6 which eaqules 9 then add the y on the end 9y
2007-12-13 11:11:06
·
answer #7
·
answered by Josh 4
·
0⤊
0⤋
the answer is the question. unless y is a number that you know (eg, y = 2- answer would be 12) then the answer can bnot be found any further
to factorise it it would be 3(y+2)
2007-12-12 15:59:11
·
answer #8
·
answered by SantasLittleHelper 2
·
0⤊
0⤋
could be anything... this isnt an equation and cannot be solved - it needs to equal something. we need something like:
3y + 6 = 0
therefore y = -2
2007-12-12 15:49:05
·
answer #9
·
answered by miggitymaggz 5
·
0⤊
0⤋
For it to be factorised it would be
3(y + 2) that's as far as you can go
2007-12-12 15:55:37
·
answer #10
·
answered by Ms. Exxclusive 5
·
0⤊
0⤋